Penatalaksanaan Gangguan Afektif Bipolar Episode Kini Depresif Berat tanpa Gejala Psikotik melalui Pendekatan Kedokteran Keluarga - Syahrizal Syahrizal; Muhammad Ridho Akbar Eljatin; Yurnailis Yurnailis; Nurul Hanifah Lubis (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
Bipolar disorder is a group of affective or mood disorders characterized by depressive and manic or hypomanic periods. The prevalence of bipolar disorder is estimated to be around 10-15 per 100,000 individuals annually in the human population, with higher rates in women, which can reach up to 30 per 100,000. Comprehensive management with a family medicine approach is necessary to improve the quality of life of patients. Service activities are conducted using counseling/support for patients with bipolar affective disorder experiencing severe depressive episodes without psychotic symptoms, reviewed through self-report, collateral history, mental status examination, home visits, and secondary data obtained from patient medical records with the application of a holistic and comprehensive family medicine approach. The goal of counseling/support for patients is to increase disease awareness and improve the patient's quality of life. The results of service activities show better understanding of the disease by patients and medication adherence levels that impact therapy success. Holistic management with a family medicine approach is necessary to identify problems in various aspects and support therapy success as well as improve patient quality of life.